Factor affecting customer loyalty toward organizing an event at Melaka Stadium Corporation / Nurul Hidayah Jamaludin - Jamaludin, Nurul Hidayah (Faculty of Business and Management, 2008)
Malacca Stadium Corporation was established with the main objectives of marketing the Sport Event and offers other services for local and international. Its main function is to provide goods and quality services to enhance their customers' satisfaction with their company's motto which is "Your Satisfaction is Our Priority". The main objective of this research is to study on "Factor Affecting Customer Loyalty Toward Organizing An Event At Melaka Stadium Corporation". Further, it is to know whether customers' are loyal or not with the services offered by Malacca Stadium Corporation.